Annealing Effect on the Microstructure and Mechanical Properties of a Thin Titanium Nitride Film - Her, S.C.; Wu, C.L. (Проблемы прочности, 2014)
Titanium nitride (TiN) films were deposited by
the D.C. magnetron sputtering process on a SUS
304 steel substrate. The effect of postdeposition
annealing on the microstructure and mechanical
properties of thin TiN films was studied in detail
using atomic force microscopy, a potentiostat
and nano-indentation tests. The TiN films were
annealed at temperatures ranging from 100 to
300C. Surface roughnesses of TiN films estimated
by atomic force microscopy decreased
from 3.83 to 2.43 nm as the annealing temperatures
increased from 100 to 300°C. The
corrosion rates of the films measured by a
potentionstat in a 0.5-molar H₂SO₄ solution decreased
from 8.57•10⁻² to 4.59•10⁻² mmPY as
the annealing temperatures increased from 100
to 300°C. An increase in corrosion resistance
was attributed to an increase in hardness and a
modulus of the film with the annealing temperature.
Atomic force microscopy images of the film
revealed fine-grained morphology for TiN films
annealed at higher temperature. Experimental results
show that the mechanical properties of TiN
films could be significantly improved by annealing.
The control of the annealing process was
proved to be critical for the improvement of TiN
film properties. Методом магнетронного напыления при постоянном токе на стальную подложку SUS 304
наносили нитрид-титановые пленки. Детально исследовано влияние отжига после нанесения
пленок на микроструктуру и их механические свойства с помощью метода атомно-силовой
микроскопии, стабилизатора напряжения и наноиндентирования. Нитрид-титановые пленки
обжигали при температуре 100…300С. Шероховатость их поверхности, исследуемая методом атомно-силовой микроскопии, уменьшилась с 3,83 до 2,43 нм при повышении температуры отжига в интервале 100…300°С. Скорость коррозии пленок, измеренная с помощью
стабилизатора напряжений в 0,5%-ном молярном растворе H₂SO₄, снизилась с 8,57•10⁻² до 4,59•10⁻² мм, тогда как температура отжига повысилась с 100 до 300°С. Рост коррозионной стойкости зависит от увеличения твердости и модуля упругости пленки с температурой отжига. Исследование пленки посредством метода атомно-силовой микроскопии
показало, что нитрид титана, который обжигался при более высокой температуре, имеет
мелкозернистую структуру. Установлено, что механические свойства нитрид-титановых
пленок можно значительно улучшить путем отжига. Получил подтверждение тот факт,
что контроль процесса отжига крайне необходим для усовершенствования свойств нитридтитановых пленок. Методом магнетронного напилення під дією постійного струму на стальну підкладку
SUS 304 наносили нітрид-титанові плівки. Детально досліджено вплив відпалу після
нанесення плівок на мікроструктуру та їх механічні властивості за допомогою методу
атомно-силової мікроскопії, стабілізатора напруги і наноіндентування. Нітрид-титанові плівки випалювали за температури 100...300C. Шорсткість їхньої поверхні, що
досліджувалася методом атомно-силової мікроскопії, зменшилася з 3,83 до 2,43 нм із
підвищенням температури відпалу в інтервалі 100...300°С. Швидкість корозії плівок,
яку вимірювали за допомогою стабілізатора напруги в 0,5%-ному молярному розчині
H₂SO₄, зменшилася з 8,57•10⁻² до 4,59 •0⁻² мм, у той час як температура відпалу підвищилась із 100 до 300°C. Зростання корозійної стійкості залежить від збільшення твердості і модуля пружності плівки з температурою відпалу. Дослідження
плівки за допомогою методу атомно-силової мікроскопії показало, що нітрид титану,
який випалювався за більш високої температури, має дрібнозеренну структуру. Установлено, що механічні властивості нітрид-титанових плівок можна значно покращити шляхом відпалу. Отримав підтвердження той факт, що контроль процесу
відпалу необхідний для удосконалення властивостей нітрид-титанових плівок.